2021
DOI: 10.3389/fphar.2021.717529
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin has New Application in Inhibiting Colorectal Cancer Cell Growth

Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide and still lacks effective therapy. Ivermectin, an antiparasitic drug, has been shown to possess anti-inflammation, anti-virus, and antitumor properties. However, whether ivermectin affects CRC is still unclear. The objective of this study was to evaluate the influence of ivermectin on CRC using CRC cell lines SW480 and SW1116. We used CCK-8 assay to determine the cell viability, used an optical microscope to measure cell morphology, used Annexin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…1). This finding is consistent with that of previous studies 5 - 7 . Notably, a previous study demonstrated that low ivermectin concentrations had no cytotoxic effect, whereas ivermectin at a concentration of ≥20 μM slightly inhibited the viability of normal cells after a 48 h exposure 6 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…1). This finding is consistent with that of previous studies 5 - 7 . Notably, a previous study demonstrated that low ivermectin concentrations had no cytotoxic effect, whereas ivermectin at a concentration of ≥20 μM slightly inhibited the viability of normal cells after a 48 h exposure 6 .…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, we demonstrated that ivermectin could induce caspase-dependent apoptosis in human UC cells. This finding is consistent with that of previous studies that used ivermectin to treat leukemia, glioblastoma, cad cervical, and colorectal cancer cells 7 , 17 , 20 - 23 . However, it could not induce cellular apoptosis in human breast cancer cells 24 , suggesting that ivermectin-induced apoptosis is not a general effect in human cancers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Oxidative stress plays a predominant role in various cancers (Arfin et al, 2021) as the excessive accumulation of ROS can induce mitochondrial dysfunction and apoptosis (Garrido et al, 2006;Zhang et al, 2016). Ivermectin promotes programmed cell death via ROS production (Tang et al, 2021;Zhou et al, 2021), and gemcitabine induces DNA damage via ROS (Wang X. et al, 2020). In renal cancer, ivermectin promotes programmed cell death via mitochondrial dysfunction caused by ROS generation (Zhu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There have been con rmed the potential role of azithromycin in the treatment of CRC [6] . Ivermectin inhibits cell proliferation by promoting ROS-mediated mitochondrial apoptosis pathway and inducing S-phase arrest in CRC cells, while inhibiting breast cancer cell growth and inducing glioblastoma cell death in vitro and in vivo [7,8] .…”
Section: Introductionmentioning
confidence: 99%